2015
DOI: 10.3126/jist.v19i2.13845
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Seasonal Variation of Arsenic in Groundwater of the Kathmandu Valley, Nepal

Abstract: A study was conducted in forty-one deep groundwater and twenty shallow groundwater wells of Kathmandu Valley, Nepal to assess arsenic contamination (shallow and deep groundwater) and spatial and seasonal variation in deep groundwater. The depths of the wells were ranged from 9 to 304 m. Groundwater samples were collected during pre monsoon and post monsoon in 2012. Atomic Absorption Spectrometer (AAS) was used to measure the concentration of arsenic. In pre monsoon and post monsoon, 36.59 % and 31.70 % of deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A periodic assessment on arsenic concentration depicts no association with seasonal variations, while repeated assessment of arsenic contents in water based on seasons is assumed to bring little value in health surveillance [ 18 ]. In contrast, seasonal and spatial variations of arsenic concentrations in groundwater have been reported by Shrestha et al [ 19 ].…”
Section: Discussionmentioning
confidence: 90%
“…A periodic assessment on arsenic concentration depicts no association with seasonal variations, while repeated assessment of arsenic contents in water based on seasons is assumed to bring little value in health surveillance [ 18 ]. In contrast, seasonal and spatial variations of arsenic concentrations in groundwater have been reported by Shrestha et al [ 19 ].…”
Section: Discussionmentioning
confidence: 90%
“…Similar study revealed that the ground water resource in the valley is contaminated with arsenic in deep aquifers [13]. Likewise, other studies have reported elevated levels of arsenic in groundwater of the valley [14]- [19]. Arsenic in groundwater wells in the Kathmandu Valley is one of the major environmental issues due to its negative health impact and more than 50% of water supply in the valley is derived from groundwater resources.…”
Section: Introductionmentioning
confidence: 70%
“…In some years of supervision was found out exceeding of an average annual regional level of morbidity I class of diseases in the following districts: Apostolivskyi (in 1.09-1.14 times The cross-correlation analysis have to find out a possible influence of water factor on an infectious and parasitogenic morbidity among the children population in some rural districts of Dnipro region. In contrast with references for the recent years [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], we did not found health effects of higher levels of iron, manganese and arsenic in water from shallow tube wells on the children population morbidity, such as: arsenicosis, skin diseases, skin cancers, internal cancers (bladder, kidney, and lung), diabetes, raised blood pressure, and reproductive disorders, children's cognitive [44], behavioral, and neuropsychological health disorders [45]. In our research work the majority of water factors, as well as general regidity, dry remain, chlorides, sulfates, calcium, magnesium, except iron, pH, nitrates, oxidableness were correlated with prevalence of infectious and parasitogenic diseases.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, seasonal and spatial variations of arsenic concentrations in groundwater have been reported by Shrestha et al [26]. Napacho and Manyele [27] found that pH values in shallow tube wells varied between 6.7 and 8.3 due to dissolved minerals from the soil and rocks.…”
Section: Introductionmentioning
confidence: 91%